(untitled) (Global Journal of Management and Business Research, 2016)
Consumer Behavior is a study of how individuals make decisions to spend their available resources like time, money and effort on consumption related items what they buy, why they buy, when they buy , where they buy, how often they buy and use a product or service for satisfying their needs. From a marketing point of view, the consumer behavior is, "the psychology of how consumers think, feel, reason and select between different alternatives like brands, products". The consumer switching behavior is there in between both, companies and customers, because the consumer switching behavior restricts both parties to make long term relationships and even it breaks the pre-developed long term relationships. Similarly the consumer switching behavior is basically the behavior of consumers in shifting their attitude from one brand (product) to another brand (product). Due to this dramatic growth, the cellular industry all over the world has been witnessing fall in the costs of cellular services, very high growth rates in subscriber base, and increasing competition and deregulation.